An urban medical system's exploratory study of medication errors - Skip G. Morelock; Jeffrey D. Kirk (Wiley, 2019)
Abstract Aims This study sought to identify patterns of medication errors with respect to shifts, day of week, unit involved, severity, medication class and cause of errors and to propose possible solutions. Design This was a retrospective explorative study using a database containing 605 medication events from two medical centres. Variables assessed include medication type, the error severity, and time the medication was ordered, the unit that the error occurred on and the day of the week of the errors. Methods Simple percentages were used to report the results, and point‐biserial correlation was employed to test for significant differences between the day and night shifts. Results There were no statistically significant findings when comparing event severity against the a.m. or p.m. shifts. The medication classes with the most errors were antibiotics, and the most common reason cited for errors was dose omission. The most commonly reported severity level was a 2 which requires increased patient monitoring.